The role of brand representatives in predicting trust in early buyer–supplier relationships. Issue 7 (3rd December 2020) - Seyedghorban, Zahra; Simpson, Dayna; Matanda, Margaret Jekanyika
Abstract : Purpose: The purpose of this study is to explore the dynamics of trust creation in an early buyer–supplier relationship phase at the interpersonal level. The authors use a brand-based communication approach to investigate the trust–risk–commitment link. Design/methodology/approach: Survey data from 204 senior managers in small and medium-size enterprises (SMEs) in Australia were collected and analyzed. Findings: Results indicate that ability, credibility, benevolence and persona of supplier brand representatives (SBRs) relate significantly to a buyers' trust in SBR, leading to diminished perceived risk, and increased relationship commitment between the parties. These findings support the importance of using individual representatives who are able to broadcast their supplier's brand values, and increase trust in exploratory buyer–supplier relationships. Research limitations/implications: This research focused on SMEs in Australia, investigating exploratory phase of the interpersonal relationships. Future research can investigate large firms interacting in different relationship phases in the light of brand-based communication. Practical implications: The study describes several strategies for both buying and supplying firms to use, to best use brand-based communication as a means to build trust in the early phases of buyer–supplier relationships. Originality/value: Prior research has focused on interorganizational trust and established or mature buyer–supplier relationships. This study investigates the initial phase of buyer–supplier relationships, and at the interpersonal exchange level. It also incorporates a role for brand-based communication in the buyer–supplier relationship which has received limited attention in the literature.